Bean’s syndrome (blue rubber bleb nevus syndrome – BRBNS) as a gastrointestinal bleeding – case report and review of the literature - Lenarcik, Małgorzata; Pachlewski, Jacek; Mróz, Andrzej (Polish Journal of Pathology, 2021)
BRBNS is a rare syndrome of vascular malformations caused by the TEK mutation associated with numerous lesions of the skin and gastrointestinal tract. We present a case report of 41 year old man with severe anemia with recurrent bleedings. The detailed clinical, endoscopical and histopathological description is given as a wide range of differential diagnosis of vascular lesions based on pathophysiology and updated classification of vascular lesions. Clinicopathological diagnosis and treatment options of BRBNS are discussed.